The Fight for the Power and the Other One in Politics - Jashari, Hasan (European Journal of Multidisciplinary Studies, 2019)
In politics we will always have friends, opponents and outsiders. They constantly appear to us and at that moment when we have won one and as such has lost the support of the electorate. But political struggle goes on with other people who use the loss of one to take his post in the electorate. But even the opposition has its announced and not announced opponents. The purpose of this research is that through the theoretical and empirical elaboration of the topic we will collect data on the political power struggle between the four main political parties in Macedonia. By means of statistical data, previous surveys and surveys of 100 students we will analyze various indicators and will make their interpretation. Today, in our political and social level, we all work against one another. To work against others, strategies must be prepared to carry out self-proclaiming to the people, how to deface the opponent, how to elaborate, reveal discoveries about the shortcomings and weaknesses of the enemy camp. It is summed up in the goals - to have information that the other is corrupt, unable,so that we can attack. But the question is that working against others is it becoming a political philosophy and permanent strategy,is it becoming a business, but also a struggle without any moral boundaries, especially in Macedonia but also in Albania and Kosovo.
Keywords: power, majority, minority, political parties, the other1.